{-# OPTIONS --without-K --safe #-}
module Definition.Conversion.Decidable where
open import Definition.Untyped
open import Definition.Typed
open import Definition.Typed.Properties
open import Definition.Conversion
open import Definition.Conversion.Whnf
open import Definition.Conversion.Soundness
open import Definition.Conversion.Symmetry
open import Definition.Conversion.Stability
open import Definition.Conversion.Conversion
open import Definition.Typed.Consequences.Syntactic
open import Definition.Typed.Consequences.Substitution
open import Definition.Typed.Consequences.Injectivity
open import Definition.Typed.Consequences.Reduction
open import Definition.Typed.Consequences.Equality
open import Definition.Typed.Consequences.Inequality as IE
open import Definition.Typed.Consequences.NeTypeEq
open import Definition.Typed.Consequences.SucCong
open import Tools.Nat
open import Tools.Product
open import Tools.Empty
open import Tools.Nullary
import Tools.PropositionalEquality as PE
strongVarEq : ∀ {m n A Γ} → Γ ⊢ var n ~ var m ↑ A → n PE.≡ m
strongVarEq (var x x≡y) = x≡y
mutual
dec~↑-app : ∀ {k k₁ l l₁ F F₁ G G₁ B Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ k ∷ Π F ▹ G
→ Δ ⊢ k₁ ∷ Π F₁ ▹ G₁
→ Γ ⊢ k ~ k₁ ↓ B
→ Dec (Γ ⊢ l [conv↑] l₁ ∷ F)
→ Dec (∃ λ A → Γ ⊢ k ∘ l ~ k₁ ∘ l₁ ↑ A)
dec~↑-app Γ≡Δ k k₁ k~k₁ (yes p) =
let whnfA , neK , neL = ne~↓ k~k₁
⊢A , ⊢k , ⊢l = syntacticEqTerm (soundness~↓ k~k₁)
ΠFG₁≡A = neTypeEq neK k ⊢k
H , E , A≡ΠHE = Π≡A ΠFG₁≡A whnfA
F≡H , G₁≡E = injectivity (PE.subst (λ x → _ ⊢ _ ≡ x) A≡ΠHE ΠFG₁≡A)
in yes (E [ _ ] , app (PE.subst (λ x → _ ⊢ _ ~ _ ↓ x) A≡ΠHE k~k₁)
(convConvTerm p F≡H))
dec~↑-app Γ≡Δ k₂ k₃ k~k₁ (no ¬p) =
no (λ { (_ , app x x₁) →
let whnfA , neK , neL = ne~↓ x
⊢A , ⊢k , ⊢l = syntacticEqTerm (soundness~↓ x)
ΠFG≡ΠF₂G₂ = neTypeEq neK k₂ ⊢k
F≡F₂ , G≡G₂ = injectivity ΠFG≡ΠF₂G₂
in ¬p (convConvTerm x₁ (sym F≡F₂)) })
dec~↑ : ∀ {k l R T Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ k ~ k ↑ R → Δ ⊢ l ~ l ↑ T
→ Dec (∃ λ A → Γ ⊢ k ~ l ↑ A)
dec~↑ Γ≡Δ (var {n} x₂ x≡y) (var {m} x₃ x≡y₁) with n ≟ m
dec~↑ Γ≡Δ (var {n} x₂ x≡y) (var .{n} x₃ x≡y₁) | yes PE.refl = yes (_ , var x₂ x≡y₁)
dec~↑ Γ≡Δ (var x₂ x≡y) (var x₃ x≡y₁) | no ¬p = no (λ { (A , k~l) → ¬p (strongVarEq k~l) })
dec~↑ Γ≡Δ (var x₁ x≡y) (app x₂ x₃) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (var x₁ x≡y) (natrec x₂ x₃ x₄ x₅) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (app x₁ x₂) (var x₃ x≡y) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (app x x₁) (app x₂ x₃)
with dec~↓ Γ≡Δ x x₂
dec~↑ Γ≡Δ (app x x₁) (app x₂ x₃) | yes (A , k~l) =
let whnfA , neK , neL = ne~↓ k~l
⊢A , ⊢k , ⊢l = syntacticEqTerm (soundness~↓ k~l)
_ , ⊢l₁ , _ = syntacticEqTerm (soundness~↓ x)
_ , ⊢l₂ , _ = syntacticEqTerm (soundness~↓ x₂)
ΠFG≡A = neTypeEq neK ⊢l₁ ⊢k
ΠF′G′≡A = neTypeEq neL (stabilityTerm (symConEq Γ≡Δ) ⊢l₂) ⊢l
F≡F′ , G≡G′ = injectivity (trans ΠFG≡A (sym ΠF′G′≡A))
in dec~↑-app Γ≡Δ ⊢l₁ ⊢l₂ k~l (decConv↑TermConv Γ≡Δ F≡F′ x₁ x₃)
dec~↑ Γ≡Δ (app x x₁) (app x₂ x₃) | no ¬p =
no (λ { (_ , app x₄ x₅) → ¬p (_ , x₄) })
dec~↑ Γ≡Δ (app x x₁) (natrec x₂ x₃ x₄ x₅) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (natrec x₁ x₂ x₃ x₄) (var x₅ x≡y) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (app x₄ x₅) = no (λ { (_ , ()) })
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇)
with decConv↑ (Γ≡Δ ∙ refl (ℕ (wfEqTerm (soundness~↓ x₃)))) x x₄
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇) | yes p
with decConv↑TermConv Γ≡Δ
(substTypeEq (soundnessConv↑ p)
(refl (zero (wfEqTerm (soundness~↓ x₃)))))
x₁ x₅
| decConv↑TermConv Γ≡Δ (sucCong (soundnessConv↑ p)) x₂ x₆
| dec~↓ Γ≡Δ x₃ x₇
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇)
| yes p | yes p₁ | yes p₂ | yes (A , k~l) =
let whnfA , neK , neL = ne~↓ k~l
⊢A , ⊢k , ⊢l = syntacticEqTerm (soundness~↓ k~l)
_ , ⊢l∷ℕ , _ = syntacticEqTerm (soundness~↓ x₃)
⊢ℕ≡A = neTypeEq neK ⊢l∷ℕ ⊢k
A≡ℕ = ℕ≡A ⊢ℕ≡A whnfA
k~l′ = PE.subst (λ x → _ ⊢ _ ~ _ ↓ x) A≡ℕ k~l
in yes (_ , natrec p p₁ p₂ k~l′)
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇)
| yes p | yes p₁ | yes p₂ | no ¬p =
no (λ { (_ , natrec x₈ x₉ x₁₀ x₁₁) → ¬p (_ , x₁₁) })
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇)
| yes p | yes p₁ | no ¬p | r =
no (λ { (_ , natrec x₈ x₉ x₁₀ x₁₁) → ¬p x₁₀ })
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇)
| yes p | no ¬p | w | r =
no (λ { (_ , natrec x₈ x₉ x₁₀ x₁₁) → ¬p x₉ })
dec~↑ Γ≡Δ (natrec x x₁ x₂ x₃) (natrec x₄ x₅ x₆ x₇) | no ¬p =
no (λ { (_ , natrec x₈ x₉ x₁₀ x₁₁) → ¬p x₈ })
dec~↓ : ∀ {k l R T Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ k ~ k ↓ R → Δ ⊢ l ~ l ↓ T
→ Dec (∃ λ A → Γ ⊢ k ~ l ↓ A)
dec~↓ Γ≡Δ ([~] A D whnfB k~l) ([~] A₁ D₁ whnfB₁ k~l₁) with dec~↑ Γ≡Δ k~l k~l₁
dec~↓ Γ≡Δ ([~] A D whnfB k~l) ([~] A₁ D₁ whnfB₁ k~l₁) | yes (B , k~l₂) =
let ⊢B , _ , _ = syntacticEqTerm (soundness~↑ k~l₂)
C , whnfC , D′ = whNorm ⊢B
in yes (C , [~] B (red D′) whnfC k~l₂)
dec~↓ Γ≡Δ ([~] A D whnfB k~l) ([~] A₁ D₁ whnfB₁ k~l₁) | no ¬p =
no (λ { (A₂ , [~] A₃ D₂ whnfB₂ k~l₂) → ¬p (A₃ , k~l₂) })
decConv↑ : ∀ {A B Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ A [conv↑] A → Δ ⊢ B [conv↑] B
→ Dec (Γ ⊢ A [conv↑] B)
decConv↑ Γ≡Δ ([↑] A′ B′ D D′ whnfA′ whnfB′ A′<>B′)
([↑] A″ B″ D₁ D″ whnfA″ whnfB″ A′<>B″)
rewrite whrDet* (D , whnfA′) (D′ , whnfB′)
| whrDet* (D₁ , whnfA″) (D″ , whnfB″)
with decConv↓ Γ≡Δ A′<>B′ A′<>B″
decConv↑ Γ≡Δ ([↑] A′ B′ D D′ whnfA′ whnfB′ A′<>B′)
([↑] A″ B″ D₁ D″ whnfA″ whnfB″ A′<>B″) | yes p =
yes ([↑] B′ B″ D′ (stabilityRed* (symConEq Γ≡Δ) D″) whnfB′ whnfB″ p)
decConv↑ Γ≡Δ ([↑] A′ B′ D D′ whnfA′ whnfB′ A′<>B′)
([↑] A″ B″ D₁ D″ whnfA″ whnfB″ A′<>B″) | no ¬p =
no (λ { ([↑] A‴ B‴ D₂ D‴ whnfA‴ whnfB‴ A′<>B‴) →
let A‴≡B′ = whrDet* (D₂ , whnfA‴) (D′ , whnfB′)
B‴≡B″ = whrDet* (D‴ , whnfB‴)
(stabilityRed* (symConEq Γ≡Δ) D″ , whnfB″)
in ¬p (PE.subst₂ (λ x y → _ ⊢ x [conv↓] y) A‴≡B′ B‴≡B″ A′<>B‴) })
decConv↓ : ∀ {A B Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ A [conv↓] A → Δ ⊢ B [conv↓] B
→ Dec (Γ ⊢ A [conv↓] B)
decConv↓ Γ≡Δ (U-refl x) (U-refl x₁) = yes (U-refl x)
decConv↓ Γ≡Δ (U-refl x) (ℕ-refl x₁) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (U-refl x) (ne x₁) =
no (λ x₂ → let whnfA , neK , neL = ne~↓ x₁
in ⊥-elim (IE.U≢ne neK (soundnessConv↓ x₂)))
decConv↓ Γ≡Δ (U-refl x) (Π-cong x₁ x₂ x₃) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (ℕ-refl x) (U-refl x₁) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (ℕ-refl x) (ℕ-refl x₁) = yes (ℕ-refl x)
decConv↓ Γ≡Δ (ℕ-refl x) (ne x₁) =
no (λ x₂ → let whnfA , neK , neL = ne~↓ x₁
in ⊥-elim (IE.ℕ≢ne neK (soundnessConv↓ x₂)))
decConv↓ Γ≡Δ (ℕ-refl x) (Π-cong x₁ x₂ x₃) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (ne x) (U-refl x₁) =
no (λ x₂ → let whnfA , neK , neL = ne~↓ x
in ⊥-elim (IE.U≢ne neK (sym (soundnessConv↓ x₂))))
decConv↓ Γ≡Δ (ne x) (ℕ-refl x₁) =
no (λ x₂ → let whnfA , neK , neL = ne~↓ x
in ⊥-elim (IE.ℕ≢ne neK (sym (soundnessConv↓ x₂))))
decConv↓ Γ≡Δ (ne x) (ne x₁) with dec~↓ Γ≡Δ x x₁
decConv↓ Γ≡Δ (ne x) (ne x₁) | yes (A , k~l) =
let whnfA , neK , neL = ne~↓ k~l
⊢A , ⊢k , _ = syntacticEqTerm (soundness~↓ k~l)
_ , ⊢k∷U , _ = syntacticEqTerm (soundness~↓ x)
⊢U≡A = neTypeEq neK ⊢k∷U ⊢k
A≡U = U≡A ⊢U≡A
k~l′ = PE.subst (λ x → _ ⊢ _ ~ _ ↓ x) A≡U k~l
in yes (ne k~l′)
decConv↓ Γ≡Δ (ne x) (ne x₁) | no ¬p =
no (λ x₂ → ¬p (U , decConv↓-ne x₂ x))
decConv↓ Γ≡Δ (ne x) (Π-cong x₁ x₂ x₃) =
no (λ x₄ → let whnfA , neK , neL = ne~↓ x
in ⊥-elim (IE.Π≢ne neK (sym (soundnessConv↓ x₄))))
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (U-refl x₃) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (ℕ-refl x₃) = no (λ { (ne ([~] A D whnfB ())) })
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (ne x₃) =
no (λ x₄ → let whnfA , neK , neL = ne~↓ x₃
in ⊥-elim (IE.Π≢ne neK (soundnessConv↓ x₄)))
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (Π-cong x₃ x₄ x₅)
with decConv↑ Γ≡Δ x₁ x₄
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (Π-cong x₃ x₄ x₅) | yes p
with decConv↑ (Γ≡Δ ∙ soundnessConv↑ p) x₂ x₅
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (Π-cong x₃ x₄ x₅) | yes p | yes p₁ =
yes (Π-cong x p p₁)
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (Π-cong x₃ x₄ x₅) | yes p | no ¬p =
no (λ { (ne ([~] A D whnfB ())) ; (Π-cong x₆ x₇ x₈) → ¬p x₈ })
decConv↓ Γ≡Δ (Π-cong x x₁ x₂) (Π-cong x₃ x₄ x₅) | no ¬p =
no (λ { (ne ([~] A D whnfB ())) ; (Π-cong x₆ x₇ x₈) → ¬p x₇ })
decConv↓-ne : ∀ {A B Γ}
→ Γ ⊢ A [conv↓] B
→ Γ ⊢ A ~ A ↓ U
→ Γ ⊢ A ~ B ↓ U
decConv↓-ne (U-refl x) A~A = A~A
decConv↓-ne (ℕ-refl x) A~A = A~A
decConv↓-ne (ne x) A~A = x
decConv↓-ne (Π-cong x x₁ x₂) ([~] A D whnfB ())
decConv↑Term : ∀ {t u A Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ t [conv↑] t ∷ A → Δ ⊢ u [conv↑] u ∷ A
→ Dec (Γ ⊢ t [conv↑] u ∷ A)
decConv↑Term Γ≡Δ ([↑]ₜ B t′ u′ D d d′ whnfB whnft′ whnfu′ t<>u)
([↑]ₜ B₁ t″ u″ D₁ d₁ d″ whnfB₁ whnft″ whnfu″ t<>u₁)
rewrite whrDet* (D , whnfB) (stabilityRed* (symConEq Γ≡Δ) D₁ , whnfB₁)
| whrDet*Term (d , whnft′) (d′ , whnfu′)
| whrDet*Term (d₁ , whnft″) (d″ , whnfu″)
with decConv↓Term Γ≡Δ t<>u t<>u₁
decConv↑Term Γ≡Δ ([↑]ₜ B t′ u′ D d d′ whnfB whnft′ whnfu′ t<>u)
([↑]ₜ B₁ t″ u″ D₁ d₁ d″ whnfB₁ whnft″ whnfu″ t<>u₁)
| yes p =
let Δ≡Γ = symConEq Γ≡Δ
in yes ([↑]ₜ B₁ u′ u″ (stabilityRed* Δ≡Γ D₁)
d′ (stabilityRed*Term Δ≡Γ d″) whnfB₁ whnfu′ whnfu″ p)
decConv↑Term Γ≡Δ ([↑]ₜ B t′ u′ D d d′ whnfB whnft′ whnfu′ t<>u)
([↑]ₜ B₁ t″ u″ D₁ d₁ d″ whnfB₁ whnft″ whnfu″ t<>u₁)
| no ¬p =
no (λ { ([↑]ₜ B₂ t‴ u‴ D₂ d₂ d‴ whnfB₂ whnft‴ whnfu‴ t<>u₂) →
let B₂≡B₁ = whrDet* (D₂ , whnfB₂)
(stabilityRed* (symConEq Γ≡Δ) D₁ , whnfB₁)
t‴≡u′ = whrDet*Term (d₂ , whnft‴)
(PE.subst (λ x → _ ⊢ _ ⇒* _ ∷ x) (PE.sym B₂≡B₁) d′
, whnfu′)
u‴≡u″ = whrDet*Term (d‴ , whnfu‴)
(PE.subst (λ x → _ ⊢ _ ⇒* _ ∷ x)
(PE.sym B₂≡B₁)
(stabilityRed*Term (symConEq Γ≡Δ) d″)
, whnfu″)
in ¬p (PE.subst₃ (λ x y z → _ ⊢ x [conv↓] y ∷ z)
t‴≡u′ u‴≡u″ B₂≡B₁ t<>u₂) })
decConv↓Term-ℕ-ins : ∀ {t u Γ}
→ Γ ⊢ t [conv↓] u ∷ ℕ
→ Γ ⊢ t ~ t ↓ ℕ
→ Γ ⊢ t ~ u ↓ ℕ
decConv↓Term-ℕ-ins (ℕ-ins x) t~t = x
decConv↓Term-ℕ-ins (ne-ins x x₁ () x₃) t~t
decConv↓Term-ℕ-ins (zero-refl x) ([~] A D whnfB ())
decConv↓Term-ℕ-ins (suc-cong x) ([~] A D whnfB ())
decConv↓Term-ne-ins : ∀ {t u A Γ}
→ Neutral A
→ Γ ⊢ t [conv↓] u ∷ A
→ ∃ λ B → Γ ⊢ t ~ u ↓ B
decConv↓Term-ne-ins () (ℕ-ins x)
decConv↓Term-ne-ins neA (ne-ins x x₁ x₂ x₃) = _ , x₃
decConv↓Term-ne-ins () (univ x x₁ x₂)
decConv↓Term-ne-ins () (zero-refl x)
decConv↓Term-ne-ins () (suc-cong x)
decConv↓Term-ne-ins () (η-eq x x₁ x₂ x₃ x₄ x₅)
decConv↓Term-ℕ : ∀ {t u Γ}
→ Γ ⊢ t [conv↓] u ∷ ℕ
→ Γ ⊢ t ~ t ↓ ℕ
→ ¬ (Γ ⊢ t ~ u ↓ ℕ)
→ ⊥
decConv↓Term-ℕ (ℕ-ins x) t~t ¬u~u = ¬u~u x
decConv↓Term-ℕ (ne-ins x x₁ () x₃) t~t ¬u~u
decConv↓Term-ℕ (zero-refl x) ([~] A D whnfB ()) ¬u~u
decConv↓Term-ℕ (suc-cong x) ([~] A D whnfB ()) ¬u~u
decConv↓Term : ∀ {t u A Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ t [conv↓] t ∷ A → Δ ⊢ u [conv↓] u ∷ A
→ Dec (Γ ⊢ t [conv↓] u ∷ A)
decConv↓Term Γ≡Δ (ℕ-ins x) (ℕ-ins x₁) with dec~↓ Γ≡Δ x x₁
decConv↓Term Γ≡Δ (ℕ-ins x) (ℕ-ins x₁) | yes (A , k~l) =
let whnfA , neK , neL = ne~↓ k~l
⊢A , ⊢k , ⊢l = syntacticEqTerm (soundness~↓ k~l)
_ , ⊢l∷ℕ , _ = syntacticEqTerm (soundness~↓ x)
⊢ℕ≡A = neTypeEq neK ⊢l∷ℕ ⊢k
A≡ℕ = ℕ≡A ⊢ℕ≡A whnfA
k~l′ = PE.subst (λ x → _ ⊢ _ ~ _ ↓ x) A≡ℕ k~l
in yes (ℕ-ins k~l′)
decConv↓Term Γ≡Δ (ℕ-ins x) (ℕ-ins x₁) | no ¬p =
no (λ x₂ → ¬p (ℕ , decConv↓Term-ℕ-ins x₂ x))
decConv↓Term Γ≡Δ (ℕ-ins x) (ne-ins x₁ x₂ () x₄)
decConv↓Term Γ≡Δ (ℕ-ins x) (zero-refl x₁) =
no (λ x₂ → decConv↓Term-ℕ x₂ x (λ { ([~] A D whnfB ()) }))
decConv↓Term Γ≡Δ (ℕ-ins x) (suc-cong x₁) =
no (λ x₂ → decConv↓Term-ℕ x₂ x (λ { ([~] A D whnfB ()) }))
decConv↓Term Γ≡Δ (ne-ins x x₁ () x₃) (ℕ-ins x₄)
decConv↓Term Γ≡Δ (ne-ins x x₁ x₂ x₃) (ne-ins x₄ x₅ x₆ x₇)
with dec~↓ Γ≡Δ x₃ x₇
decConv↓Term Γ≡Δ (ne-ins x x₁ x₂ x₃) (ne-ins x₄ x₅ x₆ x₇) | yes (A , k~l) =
yes (ne-ins x₁ (stabilityTerm (symConEq Γ≡Δ) x₄) x₆ k~l)
decConv↓Term Γ≡Δ (ne-ins x x₁ x₂ x₃) (ne-ins x₄ x₅ x₆ x₇) | no ¬p =
no (λ x₈ → ¬p (decConv↓Term-ne-ins x₆ x₈))
decConv↓Term Γ≡Δ (ne-ins x x₁ () x₃) (univ x₄ x₅ x₆)
decConv↓Term Γ≡Δ (ne-ins x x₁ () x₃) (zero-refl x₄)
decConv↓Term Γ≡Δ (ne-ins x x₁ () x₃) (suc-cong x₄)
decConv↓Term Γ≡Δ (ne-ins x x₁ () x₃) (η-eq x₄ x₅ x₆ x₇ x₈ x₉)
decConv↓Term Γ≡Δ (univ x x₁ x₂) (ne-ins x₃ x₄ () x₆)
decConv↓Term Γ≡Δ (univ x x₁ x₂) (univ x₃ x₄ x₅)
with decConv↓ Γ≡Δ x₂ x₅
decConv↓Term Γ≡Δ (univ x x₁ x₂) (univ x₃ x₄ x₅) | yes p =
yes (univ x₁ (stabilityTerm (symConEq Γ≡Δ) x₃) p)
decConv↓Term Γ≡Δ (univ x x₁ x₂) (univ x₃ x₄ x₅) | no ¬p =
no (λ { (ne-ins x₆ x₇ () x₉)
; (univ x₆ x₇ x₈) → ¬p x₈ })
decConv↓Term Γ≡Δ (zero-refl x) (ℕ-ins x₁) =
no (λ x₂ → decConv↓Term-ℕ (symConv↓Term Γ≡Δ x₂) x₁ (λ { ([~] A D whnfB ()) }))
decConv↓Term Γ≡Δ (zero-refl x) (ne-ins x₁ x₂ () x₄)
decConv↓Term Γ≡Δ (zero-refl x) (zero-refl x₁) = yes (zero-refl x)
decConv↓Term Γ≡Δ (zero-refl x) (suc-cong x₁) =
no (λ { (ℕ-ins ([~] A D whnfB ())) ; (ne-ins x₂ x₃ () x₅) })
decConv↓Term Γ≡Δ (suc-cong x) (ℕ-ins x₁) =
no (λ x₂ → decConv↓Term-ℕ (symConv↓Term Γ≡Δ x₂) x₁ (λ { ([~] A D whnfB ()) }))
decConv↓Term Γ≡Δ (suc-cong x) (ne-ins x₁ x₂ () x₄)
decConv↓Term Γ≡Δ (suc-cong x) (zero-refl x₁) =
no (λ { (ℕ-ins ([~] A D whnfB ())) ; (ne-ins x₂ x₃ () x₅) })
decConv↓Term Γ≡Δ (suc-cong x) (suc-cong x₁) with decConv↑Term Γ≡Δ x x₁
decConv↓Term Γ≡Δ (suc-cong x) (suc-cong x₁) | yes p =
yes (suc-cong p)
decConv↓Term Γ≡Δ (suc-cong x) (suc-cong x₁) | no ¬p =
no (λ { (ℕ-ins ([~] A D whnfB ()))
; (ne-ins x₂ x₃ () x₅)
; (suc-cong x₂) → ¬p x₂ })
decConv↓Term Γ≡Δ (η-eq x x₁ x₂ x₃ x₄ x₅) (ne-ins x₆ x₇ () x₉)
decConv↓Term Γ≡Δ (η-eq x x₁ x₂ x₃ x₄ x₅) (η-eq x₆ x₇ x₈ x₉ x₁₀ x₁₁)
with decConv↑Term (Γ≡Δ ∙ refl x) x₅ x₁₁
decConv↓Term Γ≡Δ (η-eq x x₁ x₂ x₃ x₄ x₅) (η-eq x₆ x₇ x₈ x₉ x₁₀ x₁₁) | yes p =
yes (η-eq x x₂ (stabilityTerm (symConEq Γ≡Δ) x₇) x₄ x₁₀ p)
decConv↓Term Γ≡Δ (η-eq x x₁ x₂ x₃ x₄ x₅) (η-eq x₆ x₇ x₈ x₉ x₁₀ x₁₁) | no ¬p =
no (λ { (ne-ins x₁₂ x₁₃ () x₁₅)
; (η-eq x₁₂ x₁₃ x₁₄ x₁₅ x₁₆ x₁₇) → ¬p x₁₇ })
decConv↑TermConv : ∀ {t u A B Γ Δ}
→ ⊢ Γ ≡ Δ
→ Γ ⊢ A ≡ B
→ Γ ⊢ t [conv↑] t ∷ A
→ Δ ⊢ u [conv↑] u ∷ B
→ Dec (Γ ⊢ t [conv↑] u ∷ A)
decConv↑TermConv Γ≡Δ A≡B t u =
decConv↑Term Γ≡Δ t (convConvTerm u (stabilityEq Γ≡Δ (sym A≡B)))